The Effects of Canonity and the Authorial Weight in Translating Men in Sun’ Ghassan Kanafani into English Language - Khawaldeh, Heba Barghash (Technium Education and Humanities, 2024)
This study deals with canonity in the translation from Arabic to English of Authorial Weight and Translator Authority in the novella "Men in Sun". It debates that if Men in Sun "Rejal fel AL-Shamas" that written by famous author in Arab world Ghassn Kanafani Palestinian writer that defend on the Palestinian issue, the above mentioned novella translated to English by Dr. Hilary Kilpatrick gave the same value to the TT as it appears in the ST during translating accurately the features of figurative language idioms, religious expressions, metaphors, symbolism, and cultural items with choosing randomly examples from the novel. According to strategies found in the translation based on Vinay and Darbelnet’s (1995) including direct and Oblique translation and Newmark’s (1988). moreover, the study stresses the value of perception the goal, emotiveness, ideology embedded in Arabic novel Men in Sun "Rejal fel AL-Shamas" when the translator seeks to equal between the TT and ST. The aesthetic features that notable in Arabic that really the translator attempts to reddened it in English to give the sense of the sentences. In short, involves that the translation of literally work is affected by the canonity and aesthetic features that applied.